Sengketa Tapal Batas Antar Daerah Otonom di Indonesia: Studi Kasus di Provinsi Riau - Mahmuzar - Mahmuzar (Fakultas Hukum Universitas Islam Indonesia, 2018)
This study aimed to find out about the causes of boundary disputes between autonomous regions in Indonesia, especially in Riau Province, and the procedures for the settlement. This was a socio-legal research, i.e. analyzing the law that exists in a community. This study used both primary and secondary legal materials, obtained through field surveys, library research, and interviews with key informants. The results of this study showed that the boundary disputes between autonomous regions in Indonesia, especially in Riau Province, are caused by: First, the boundary markers are located far from each other; Second, there is custody of government and citizenship administrative services; Third, the interests of capital owners and; Fourth, political interests. The settlement of the boundary disputes between autonomous regions in Indonesia, especially in Riau Province, is through the decision of the state officials/administrative authorities and court decisions i.e.: decision of the State Administrative Court and the Constitutional Court